Meningkatkan Hasil Belajar Siswa Pada Pembelajaran Seni Budaya (Seni Tari) Di SMPN 2 Sungai Geringging Melalui Metode Talking Stick - Diva Nia Zulnita; Marzam Marzam (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
The study aims to determine the improvement of student learning outcomes in learning cultural arts (dance) using the talking stick method at SMP Negeri 2 Sungai Geringging. The type of research used is classroom action research which is classified as qualitative research. This research is carried out in two cycles, consisting of planning, implementation, observation, and reflection. The instruments of this study are observation sheets, cognitive tests, and documentation. Data analysis using percentage formulas. The results showed that the application of using the talking stick method can improve student learning outcomes in cultural arts learning. This can be seen from student activities in the learning process and the average score of written tests from cycle I to cycle II. In the first cycle of the 1st meeting, the average score of student activity of 1.28% was categorized as poor, while the 2nd meeting was 3.14% categorized as good. In the second cycle, the average score of student activity of 3.42% was categorized as very good. In the first cycle, the average score of completeness of students obtained was 45%, while those who had not achieved completeness percentage of 55%. In the second cycle of student learning outcomes obtained an average score of completeness percentage of 85%, while those who have not achieved completeness percentage of 15%. Thus, the results of this study show that the application of the talking stick method can improve student learning outcomes in cultural arts learning.